2011
DOI: 10.1186/1472-6874-11-35
|View full text |Cite
|
Sign up to set email alerts
|

"I do what I have to do to survive": An investigation into the perceptions, experiences and economic considerations of women engaged in sex work in Northern Namibia

Abstract: BackgroundThere is little published research investigating sex work in Namibia, particularly in rural areas. Therefore, the aim of this paper was to determine the views of women engaged in sex work in the Oshakati area of Namibia concerning the main factors influencing their use, or non-use, of male condoms during transactional sexual exchanges.MethodsQualitative interviews were used to better understand the perceptions, experiences and economic considerations of female sex workers in Namibia who were involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Previous studies have identified a number of factors that affect condom use among female sex workers. In a study of the perceptions and experiences of FSWs in Namibia, Fitzgerald-Husek et al 22 found that condom use prospects depended on the level of intimacy with partner, and the woman's financial standing at the time, among other factors. A study in Kinshasa found that about a quarter of sex workers reported having unprotected sex for extra money, charging up to 3.5 times more for unprotected sex 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a number of factors that affect condom use among female sex workers. In a study of the perceptions and experiences of FSWs in Namibia, Fitzgerald-Husek et al 22 found that condom use prospects depended on the level of intimacy with partner, and the woman's financial standing at the time, among other factors. A study in Kinshasa found that about a quarter of sex workers reported having unprotected sex for extra money, charging up to 3.5 times more for unprotected sex 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of multiple partnerships has been documented [See 10,11,28,15,16]. However, gaps exist in knowledge on correlates of secret multiple partnership, sex differentials and HIV risk amongst stable relationships in Tiv land.…”
Section: Resultsmentioning
confidence: 99%
“…Such sexual behaviours have been observed to be highly risky especially where condom usage is low. Sex work has attracted considerable attention [13][14][15][16][17][18]. Another type of multiple partnerships could be serial partnerships with short gaps between them, it may constitute similar risk such as posed by multiple concurrent partners, since a recently infected person may expose a new partner to HIV/STI while transmission probabilities are highest [19].…”
Section: Resultsmentioning
confidence: 99%
“…This has prompted various organisations such as UNFPA, Society for Family Health and King's Daughters to conduct outreach and assessment. Yet, the topics of age at first sex work, sex workers sharing earnings and/or being forced to share earnings has been largely absent from most recent reports (Fitzgerald-Husek et al, 2011;UNFPA, 2011c). Data from this research should shed light on these issues so that young Namibian sex workers can be better understood, empowered and aided.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, defining who is a sex worker in Namibia is problematic. Various studies have identified commercial sex workers, informal sex workers, transactional sex, survival sex and exchange-sex (Edwards, 2007;Fitzgerald-Husek et al, 2011). Further problematising the issue is who decides who is a sex worker: The researcher?…”
Section: Introductionmentioning
confidence: 99%